2018
DOI: 10.3389/fncel.2018.00411
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Hyperactivity and Age Affect Segregation and Expression of Neurotransmitters

Abstract: Sympathetic neurons of the rat superior cervical ganglion (SCG) can segregate their neurotransmitters and co-transmitters to separate varicosities of single axons. We have shown that transmitter segregation is a plastic phenomenon and that it is correlated with the strength of synaptic transmission. Here, we determined whether sympathetic dysfunction occurring in stress and hypertension was correlated with plastic changes of neurotransmitter segregation. We characterized the expression of the markers, L-glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 39 publications
5
14
0
Order By: Relevance
“…We confirmed the contribution of endogenous GABA in the expression of gLTP [30], and reported recently that GABA expression is greater in the SCG of SHR than in WKy [38]. According to the evidence that (i) heightened sympathetic nerve activity can be detected before the development of hypertension in SHR [2225], (ii) GABA can block the occurrence of LTP in rat SCG of Wistar rats [33, 34], (iii) GABA presence can increase in SCG of SHR [38], and (iv) GABA has an antihypertensive central effect in SHR [3941], we draw the following hypothesis: “early changes in neuroplasticity, particularly in the expression of gLTP, and its modulation by GABAergic inputs would be part of the mechanisms underlying neurogenic hypertension in SHR” .…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…We confirmed the contribution of endogenous GABA in the expression of gLTP [30], and reported recently that GABA expression is greater in the SCG of SHR than in WKy [38]. According to the evidence that (i) heightened sympathetic nerve activity can be detected before the development of hypertension in SHR [2225], (ii) GABA can block the occurrence of LTP in rat SCG of Wistar rats [33, 34], (iii) GABA presence can increase in SCG of SHR [38], and (iv) GABA has an antihypertensive central effect in SHR [3941], we draw the following hypothesis: “early changes in neuroplasticity, particularly in the expression of gLTP, and its modulation by GABAergic inputs would be part of the mechanisms underlying neurogenic hypertension in SHR” .…”
Section: Introductionsupporting
confidence: 88%
“…We found that evoked gLTP in 12 wo SHR was masked by endogenous GABA, because the antagonism of GABA-A receptors by bicuculline unmasked the potentiation phenomenon. In support of this role of GABA, we have recently reported a greater presence of GABA-containing sympathetic varicosities in SCG of 12 wo SHR by comparison with WKy rats [38]. This effect of endogenous GABA might be related with reports of GABAergic antihypertensive effect in SHR.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The axons of sympathetic postganglionic neurons organize the cardiac plexus and supply various parts of the heart, including the sinus node, the atrioventricular junction, the atrioventricular bundle, the atrial muscle, and the ventricular muscle. SCG and SG not only transmit sympathetic ganglion signals, but also play an integral role in the regulation of autonomic function (Tu et al, ; Liu et al, ; Zhang et al, ; Merino‐Jimenez et al, ). Thus, the cervical sympathetic ganglia can be viewed as a neural circuit that receives sensory visceral information and controls output to cardiovascular targets.…”
Section: The Heart Function Regulated By Superior Cervical Ganglia Anmentioning
confidence: 99%